2021
DOI: 10.3390/bios11020054
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Glucose on Nanostructured Gold Film Biosensor by Surface-Enhanced Raman Spectroscopy

Abstract: In this report, we summarized our development of biosensors for Rhodamine 6G and in vitro glucose detection based on surface-enhanced Raman scattering technology. For the detection of both Rhodamine 6G and in vitro glucose, a nature-patterned substrate with gold films over nanostructures (NPS-AuFON) was used as the surface-enhanced Raman scattering sensor platform. The enhancement factor was calculated at . In the processing of the substrate, cyclic voltammetry was used to form nano-gold particles under differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Upon polarization (Figure b), there is an increase in intensity of some bands and the appearance of new bands due to the formation of oxidation products of glucose at the interface (details in Figure S51). The bands at 1585 and 1615 cm –1 belong to υ as (COO – ) and those at 1440–1410 cm –1 for ν s (O–C–O) suggest the formation of a carboxylate function. Convoluted with CH 2 wagging and bending of CH 2 , , we conclude that gluconate is the main product because of the absence of CH 2 signal for glucuronate. , The band at 1720 cm –1 belongs to υ­(CO) of gluconolactone as a reactive intermediate prior to ring-opening and production of gluconate. , This study thus also reveals the exquisite sensitivity of our GDE-Au substrate for detecting intermediates adsorbed or at least in the close vicinity of the electrode, even for complex mechanisms that display only poorly Raman active intermediates.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Upon polarization (Figure b), there is an increase in intensity of some bands and the appearance of new bands due to the formation of oxidation products of glucose at the interface (details in Figure S51). The bands at 1585 and 1615 cm –1 belong to υ as (COO – ) and those at 1440–1410 cm –1 for ν s (O–C–O) suggest the formation of a carboxylate function. Convoluted with CH 2 wagging and bending of CH 2 , , we conclude that gluconate is the main product because of the absence of CH 2 signal for glucuronate. , The band at 1720 cm –1 belongs to υ­(CO) of gluconolactone as a reactive intermediate prior to ring-opening and production of gluconate. , This study thus also reveals the exquisite sensitivity of our GDE-Au substrate for detecting intermediates adsorbed or at least in the close vicinity of the electrode, even for complex mechanisms that display only poorly Raman active intermediates.…”
Section: Resultsmentioning
confidence: 78%
“…14,43 The band at 1720 cm −1 belongs to υ(C�O) of gluconolactone as a reactive intermediate prior to ring-opening and production of gluconate. 44,45 This study thus also reveals the exquisite sensitivity of our GDE-Au substrate for detecting intermediates adsorbed or at least in the close vicinity of the electrode, even for complex mechanisms that display only poorly Raman active intermediates. meV in favor of (A) with a pseudo-bridge structure while (B) has a top one (Figure 4c).…”
Section: In Situ Analysis: Electrochemical Surface-enhanced Raman Spe...mentioning
confidence: 65%
“…The results showed that the method had a high quantitative analysis capability for glucose solutions and could judge whether or not a patient is diabetic by detecting glucose concentration at a minimum (11.1 mmol L À1 ). 42 2.2. Utilization of gas sensors made of biomedical metaloxides to detect glucose in exhaled gas Nanostructured metal-oxides, such as ZnO, CuO, MnO 2 , TiO 2 , etc.…”
Section: Detection Of Glucose By Sensors or Samplers Made Of Biomedic...mentioning
confidence: 99%
“…In addition, Raman spectroscopy has its detection limits, and it is not easy to detect relatively low concentrations of biomolecules. 42 So, it is necessary to enhance the Raman signal. The sensor is modified with nanomaterials that are more sensitive and could amplify the signal of the detected object, and then the Raman analysis is performed.…”
Section: Summary and Prospectmentioning
confidence: 99%
“…Similarly, Vikulina et al [ 30 ] verified the analytical performance of porous Au micro shells for detection of Rhodamine B. Sung et al [ 31 ] used the R6G to characterize the performance of SERS substrate. These examples illustrate the importance of the detection task in biosensing applications.…”
Section: Introductionmentioning
confidence: 99%